Una defensa pluralista de la investigación jurídica - Escobar Córdoba, Federico (2023)
The main thesis of this article is that the ruling paradigm in research in Colombia is that of empirical sciences, which is why disciplines that take on different kinds of research, like law, must insist that the plural forms of academic research be respected. The argument begins by reconstructing the discussion about the scientific character of law, and suggests that many of the hopes to create a “legal science” are unduly reductive. The author then considers the way in which legal research in Colombia is dominated, conc eptually and in practice, by empirical sciences. Afterward, the article highlights the interdisciplinary quality of law, and ends with a few observations that purport to reaffirm, in research, the pluralism of academic pursuits.